Effect of Direct and Indirect Compensation on Performance of Employees PT. Terminal Petikemas Surabaya - Bagus Angan Brasilio; Hermien Tridayanti (Journal of World Conference (JWC), 2020)
The purpose of this study is to analyze the effect of direct and indirect compensation on employee performance simultaneously and partially. The population in this study was 92 employees. This study uses a quantitative approach. The object of this research is direct compensation and indirect compensation at PT. Surabaya Container Terminal. The data collection methods used were questionnaires and interviews. The data analysis technique used is multiple linear regression. The results of the study are that direct compensation has a positive and significant effect on employee performance, and indirect compensation has a positive and significant effect on employee performance. To improve employee performance, companies can maintain and improve indirect compensation services, because indirect compensation has a dominant influence in influencing employee performance, such as improving employee welfare, paying attention to what employees need now, then the company can provide indirect compensation in return for employee services that have been provided to the company.